Neurocognitive Predictors of Response in Treatment Resistant Depression to Subcallosal Cingulate Gyrus Deep Brain Stimulation - McInerney, Shane J.; McNeely, Heather E.; Geraci, Joseph; Giacobbe, Peter; Rizvi, Sakina J.; Ceniti, Amanda K.; Cyriac, Anna; Mayberg, Helen S.; Lozano, Andres M.; Kennedy, Sidney H. (Frontiers in Human Neuroscience, 2017)
BACKGROUND: Deep Brain Stimulation (DBS) is a neurosurgical intervention with demonstrated effectiveness for Treatment Resistant Depression (TRD), but longitudinal studies on the stability of cognitive parameters following treatment are limited. The objectives of this study are to (i) identify baseline cognitive predictors of treatment response to Subcallosal Cingulate Gyrus (SCG) DBS for unipolar TRD and (ii) compare neurocognitive performance prior to and 12 months after DBS implantation. METHODS: Twenty unipolar TRD patients received SCG DBS for 12 months. A standardized neuropsychological battery was used to assess a range of neurocognitive abilities at baseline and after 12 months. Severity of depression was evaluated using the 17 item Hamilton Rating Scale for Depression (HRSD-17). RESULTS: Finger Tap-Dominant Hand Test and total number of errors made on the Wisconsin Card Sorting Test predicted classification of patients as treatment responders or non-responders, and were independent of improvement in mood. Change in verbal fluency was the only neuropsychological test that correlated with change in mood from baseline to the follow up period. None of the neuropsychological measures displayed deterioration in cognitive functioning from baseline to repeat testing at 12 months. LIMITATIONS: This was an open label study with a small sample size which limits predictive analysis. Practice effects of the neuropsychological testing could explain the improvement from baseline to follow up on some tasks. Replication using a larger sample of subjects who received neuropsychological testing before and at least 12 months after DBS surgery is required. CONCLUSIONS: These preliminary results (i) suggest that psychomotor speed may be a useful baseline predictor of response to SCG DBS treatment and (ii) support previous suggestions that SCG DBS has no deleterious effects on cognition.